The Reality Of Banking Facilities And Their Impact On Supporting Foreign Trade A Field Study On Banks Operating On The Syrian Coast (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This research aims to study the reality of banking facilities in its three dimensions (general policies, guarantees, and procedures) and their impact on supporting foreign trade, for the banks operating on the Syrian coast. The researcher used the descriptive /analytical/ method to collect data based on the opinion poll, where the researcher distributed 70 questionnaires to the research sample, 56 of which were retrieved and of which 10 questionnaires were not suitable for analysis, so the total of the questionnaires valid for analysis is 46. The researcher analyzed the data using the statistical analysis program )spss20.(At the end of the research, the researcher reached several conclusions, including: There is a significant impact of banking facilities in its three dimensions (general policies, guarantees, and procedures) in support of foreign trade operations for the banks operating on the Syrian coast.The researcher presented a set of recommendations, including: Directing bank administrations to pay attention to banking facilities as an activity that contributes to supporting foreign trade, which is reflected in increasing their profits and their active role in the economy, in addition to encouraging banks to increase their support and financing for economic and productive projects because of the great importance of this in the field of Stimulating investment and directing banking facilities towards the productive and industrial sectors and reducing credit directed towards consumer facilities.